The local order and structural evolution of amorphous PdAg alloy during isothermal annealing under high pressure: A molecular dynamics study - Celik, Fatih Ahmet; Kazanc, Sefa (Canadian Science Publishing, Nrc Research Press, 2015)
In this study, the local order and the structural evolution of the PdAg binary alloy system during the crystallization process from the amorphous phase under different pressures was investigated using the molecular dynamics simulation method. The structural development and phase transformation of the model alloy system for pressures of 0, 1, and 5 GPa are analysed based on variations of the radial distribution function, the bond orientational order parameters, and Honeycutt-Andersen bond-type index method. The simulation results showed that higher pressures favoured amorphous-type atomic clusters and had an important effect on the bond orientational order parameters of the model system of the transformation from amorphous state to stable crystal phase during the isothermal annealing.
Keywords: Bond-Orientational Order; Mechanical-Properties; Thermal-Stability; Transition-Metals; Simulation; Crystallization; Cu; Potentials; Glasses; Liquids